Teachers’ Roles in Elementary Music Education for Grade V Students at SD Islam Alhidayah Besusu - Murlan, Muliati; Lagandesa, Yun Ratna; Lapasere, Sisriawan; Dewi, Andi Imrah; A.Rahmaeni M, A.Rahmaeni M (FKIP - Universitas Riau, 2025)
This research investigates the teacher’s role in music education for fifth-grade students at SD Islam Alhidayah Besusu. Recognizing that music learning at the elementary level is essential for developing students’ cognitive, affective, and psychomotor aspects, the study focuses on how teachers act as facilitators, classroom managers, motivators, supervisors, and demonstrators. Using a descriptive qualitative approach, data were collected through observation, interviews, questionnaires, and documentation involving a classroom teacher and students. Findings reveal that while the teacher has performed well as a demonstrator and class manager, several challenges persist, including limited musical instruments and the teacher’s lack of formal training in music education. Observations and student questionnaires indicate that students generally perceive the teacher’s efforts positively, especially in creating a conducive learning atmosphere and providing clear demonstrations. Statistical results from the questionnaires show that 62.5% of students state the teacher always gives clear examples before practice, and 50% feel inspired by musical works shown in class. In conclusion, despite facing resource constraints, the teacher’s proactive role significantly supports the effectiveness of music learning. It is recommended that schools provide more comprehensive training and facilities to empower teachers in delivering high-quality music education in primary schools.